Emile Zola a very short introduction - Nelson, Brian 1946- (Very short introductions, 2020)
Emile Zola occupies a distinctive place in the great tradition of French realist fiction. Brian Nelson introduces this quintessential novelist of modernity, and explores his fascination with change, and the way he opened the novel up to new areas of representation: the realities of working-class life, class relations, and sexuality and the body